New developments in the management of nonmuscle invasive bladder cancer. Issue 3 (May 2017) - Tyson, Mark D.; Lee, Daniel; Clark, Peter
Abstract : Purpose of review: In this review, we summarize the core principles in the management of nonmuscle invasive bladder cancer (NMIBC) with an emphasis on new developments that have emerged over the last year. Recent findings: NMIBC has a propensity to recur and progress. Risk stratification has facilitated appropriate patient selection for treatment but improved tools, including biomarkers, are still needed. Enhanced cystoscopy with photodynamic imaging and narrow band imaging show promise for diagnosis, risk stratification, and disease monitoring and has been formally recommended this year by the American Urological Association. Attempts at better treatment, especially in refractory high-risk cases, include the addition of intravesical hyperthermia, combination and sequential therapy with existing agents, and the use of novel agents such as mycobacterial cell wall extract. New data are emerging regarding the potential role of early cystectomy in bacillus Calmette–Guerin-refractory NMIBC patients. Summary: NMIBC represents an assortment of disease states and continues to pose management challenges. Continued research is needed to bolster the evidence needed for patients and providers to make data-driven treatment decisions.